The role of monocyte to lymphocyt ratio in predicting metastasis in rectal cancer - Catal, Oguz; Ozer, Bahri; Sit, Mustafa; Aktas, Gulali; Erkol, Hayri (Annals of Medical Research, 2021)
Aim: A lot of studies are being carried out to predict recurrence and metastasis in rectal cancer, which is a common type of cancer in general surgery practice. It is thought that MLR (monocyte to lymphocyte ratio) , an indice developed by division of monocyte count by lymphocyte count, may be a good marker to reflect the degree of tumor progression and predict prognosis. In our study, we investigated the role of MLR in predicting metastasis in rectal cancer.Materials and Methods: Fifty-seven patients diagnosed with rectal cancer in the Abant Izzet Baysal University general surgery clinic between 2012 and 2016 were retrospectively investigated. Albumin, CRP(C reactive protein), Platelet, Neutrophil, Lymphocyte, Monocyte values were obtained as the inflammatory markers in the blood count test of the patients before neoadjuvant treatment.Results: In this study, 25 patients who underwent neoadjuvant chemoradiotherapy and underwent full postoperative follow-up were evaluated. Eight of these 25 patients had metastasis until June 2019. There was a significant difference in monocyte and MLR values between groups with and without metastasis.Conclusion: This study is presented as a preliminary study. In our study, we showed that MLR value which measured before neoadjuvant therapy in rectum cancer patients may be useful in predicting metastasis development.